2018
DOI: 10.1016/j.clinmicnews.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiratory Multiplex Panels for the Detection of Bacterial and Viral Infections

Abstract: Development of commercial multiplex panels for the detection and diagnosis of lower respiratory tract infections is rapidly progressing, and FDA-cleared assays are currently available. This review provides a comprehensive overview of the current or soon-to-be available commercial assays, focusing on their analytical performance, advantages, and challenges and the potential impact on patient outcomes when laboratories deploy the assays. CMN 132 Clinical Microbiology Newsletter 40:16,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Although the use of the FAPP panel has obvious benefits for the diagnosis and management of patients with suspected pneumonia, its implementation is not without challenges. ( Alby and Mitchell, 2018 ) Firstly, the sensitivity of detection of each target may be compromised due to the diverse number of targets included in the panel. ( Alby and Mitchell, 2018 ) This was demonstrated in the study by Kerr et al (2018) that reported lower sensitivities for the detection of a number of targets in the FAPP panel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the use of the FAPP panel has obvious benefits for the diagnosis and management of patients with suspected pneumonia, its implementation is not without challenges. ( Alby and Mitchell, 2018 ) Firstly, the sensitivity of detection of each target may be compromised due to the diverse number of targets included in the panel. ( Alby and Mitchell, 2018 ) This was demonstrated in the study by Kerr et al (2018) that reported lower sensitivities for the detection of a number of targets in the FAPP panel.…”
Section: Discussionmentioning
confidence: 99%
“…( Alby and Mitchell, 2018 ) Firstly, the sensitivity of detection of each target may be compromised due to the diverse number of targets included in the panel. ( Alby and Mitchell, 2018 ) This was demonstrated in the study by Kerr et al (2018) that reported lower sensitivities for the detection of a number of targets in the FAPP panel. ( Kerr et al, 2018 ) In our analysis we also found low sensitivity for some targets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations